Adolescents' Daily Experience of Fathers' Emotional Support and Self‐Evaluation in Korea. (24th May 2019) - Cheon, Yuen Mi; Chung, Grace H.
Abstract : Recently, fathers' role in children's development has been recognized internationally. In Asian countries, similar conversations have emerged but there has been a lack of empirical studies that considered the unique cultural contexts. As a response, based on Bronfenbrenner's process‐person‐context‐time model, the present study examined the daily dynamics and individual differences in the experience of fathers' emotional support and self‐evaluation in social roles among 283 Korean adolescents in 5th and 8th grade. Through Hierarchical Linear Modeling, within‐person associations between adolescents' experience of fathers' emotional support and self‐evaluation in social roles on the same day and the next day were found, with individual differences by grade level and family affluence. Theoretical and practical implications within the relevant cultural context are discussed.